Prediction of extravasation in pelvic fracture using coagulation biomarkers - Aoki, Makoto; Hagiwara, Shuichi; Tokue, Hiroyuki; Shibuya, Kei; Kaneko, Minoru; Murata, Masato; Nakajima, Jun; Sawada, Yusuke; Isshiki, Yuta; Ichikawa, Yumi; Oshima, Kiyohiro (Injury, 2016)
To evaluate the usefulness of coagulation biomarkers, which are easy and quick to analyze in emergency settings, for prediction of arterial extravasation due to pelvic fracture. The medical records of pelvic fracture patients transferred to the emergency department of Gunma University Hospital between December 2009 and May 2015 were reviewed. Patients were divided into two groups, those with (Extra(+)) and without (Extra(−)) arterial extravasation on enhanced CT or angiography. Levels of fibrin degradation products (FDP), D-dimer, fibrinogen, the ratio of FDP to fibrinogen, the ratio of D-dimer to fibrinogen, systolic blood pressure, heart rate, the Glasgow Coma Scale, pH, base excess, hemoglobin and lactate levels, the pattern of pelvic injury, and injury severity score were measured at hospital admission, and compared between the two groups. Parameters with a significant difference between the two groups were used to construct receiver operating characteristic (ROC) curves. The study included 29 patients with pelvic fracture. FDP, D-dimer, the ratio of FDP to fibrinogen and the ratio of D-dimer to fibrinogen were the most useful parameters for predicting arterial extravasation due to pelvic fracture. FDP, D-dimer, the ratio of FDP to fibrinogen, the ratio of D-dimer to fibrinogen, and hemoglobin and lactate levels were significantly higher in the Extra(+) group than in the Extra(−) group (FDP, 354.8μg/mL [median] versus 96.6μg/mL; D-dimer, 122.3μg/mL versus 42.1μg/mL; the ratio of FDP to fibrinogen, 3.39 versus 0.42; the ratio of D-dimer to fibrinogen, 1.14 versus 0.18; hemoglobin, 10.5g/dL versus 13.5g/dL; lactate, 3.5mmol/L versus 1.7mmol/L). The area under the ROC curves for FDP, D-dimer, the ratio of FDP to fibrinogen, the ratio of D-dimer to fibrinogen, hemoglobin and lactate levels were 0.900, 0.882, 0.918, 0.900, 0.815 and 0.765, respectively. Coagulation biomarkers, and hemoglobin and lactate levels could be useful to predict the existence of arterial extravasation due to pelvic fracture. The ratio of FDP to fibrinogen and the ratio of D-dimer to fibrinogen were the most accurate markers. Coagulation biomarkers may enable more rapid and specific treatment for pelvic fracture.